PROSTHETIC REPAIR AT INCISIONEL HERNIAS (THE OUR EXPERIENCES AND RESULTS FOR 20 YEARS) - Sezai YILMAZ; Hakan ÖZEL; Osman YILDIRIM; Cenap DENER; Emin SİPAHİOĞLU; Kazım UĞUR (Turkish Journal of Gastroenterology, 2020)
-